Analisis Yuridis Penggunaan Perjanjian Pengikatan Jaminan Fidusia dan Kuasa (Ppjf) terhadap Mesin yang Masih dalam Pemesanan - Agus Andrianto (Fakultas Hukum Universitas Islam Jember, 2019)
Credit or financing based on sharia principles provided by banks carries risks, so in practice banks must pay attention to the principles of credit or financing based on sound Sharia Principles. As an intermediary institution and in line with the external and internal environment of the banking system, it is currently experiencing rapid development. Banks are required to be more flexible in providing financing / credit by accepting guarantees that will still exist in the future. One of them is through credit / financing activities based on sharia principles through instruments known in international trade transactions is a Letter of Credit (